2009
DOI: 10.1089/apc.2009.0039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Atazanavir-Ritonavir Plus Abacavir-Lamivudine or Tenofovir-Emtricitabine in Patients with Hyperlipidaemia Switched from a Stable Protease Inhibitor-Based Regimen Including One Thymidine Analogue

Abstract: Randomized, open-label, prospective clinical trial assessing efficacy and safety on hyperlipidemia of a switching from a regimen including one protease inhibitor and one thymidine analogue to atazanavir/ritonavir plus abacavir/lamivudine or tenofovir/emtricitabine. Adult HIV-infected patients on their first antiretroviral therapy (of at least 48-week duration), including one protease inhibitor and zidovudine or stavudine, with stable immunovirologic features, and having diagnosis of persisting hyperlipidemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Therefore, FTC/TDF was always compared with 3TC co‐formulated with abacavir or zidovudine in boosted PI‐based regimens (), in NNRTI‐based regimens or in INI‐based regimens . Several trials found comparable efficacies of FTC and 3TC, but randomized patients when they had already become HIV RNA suppressed on previous cART . The use of 3TC in combination with TDF in an NRTI backbone was only evaluated in three small studies in NNRTI‐based regimens, including two pilot trials without an FTC‐containing comparator arm , and one unpublished underpowered open‐label randomized trial .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FTC/TDF was always compared with 3TC co‐formulated with abacavir or zidovudine in boosted PI‐based regimens (), in NNRTI‐based regimens or in INI‐based regimens . Several trials found comparable efficacies of FTC and 3TC, but randomized patients when they had already become HIV RNA suppressed on previous cART . The use of 3TC in combination with TDF in an NRTI backbone was only evaluated in three small studies in NNRTI‐based regimens, including two pilot trials without an FTC‐containing comparator arm , and one unpublished underpowered open‐label randomized trial .…”
Section: Discussionmentioning
confidence: 99%
“…In the ACTG 5202 study, at 96 weeks, patients treated with atazanavir/r had significantly lower increases in fasting total cholesterol, LDL and HDL compared with efavirenz, regardless of the NRTI backbone used [76]. Several other studies have switched patients with suppressed HIV RNA from other PI-based cART regimens to atazanavir/r, with subsequent improvements observed in lipids (Table 5) [102107]. Using this strategy, the total cholesterol decreased from 12 to 25 mg/dl, LDL decreased from 4 to 6 mg/dl and triglycerides decreased from 38 to 182 mg/dl, depending on the population studied.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…53,6062 In fact, early in its development and use, abacavir was often prescribed to patients thought to be at risk for CHD. This predisposition was shown in the D:A:D study where 27% of patients starting abacavir had moderate or high predicted 10-year risk of CHD compared to 19% of those starting other NRTIs such as zidovudine or stavudine.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%